Factors associated with anxiety in medical interns at a private university in the context of the Covid-19 pandemic: Factores asociados a la ansiedad en internos de medicina de una universidad privada en el contexto de la pandemia Covid-19 - Cehua Alvarez, Efrain A. (2022)
OBJECTIVE: To determine the factors associated with anxiety in medical interns at a private university in the context of the covid-19 pandemic. METHODS: The study design is quantitative, observational, analytical, retrospective, cross-sectional. The sample was comprised of 343 human medicine interns, who were selected by a non-probabilistic snowball type sampling. The Coronavirus Anxiety Scale instrument was used for the diagnosis of anxiety. A Poisson regression model with robust bivariate and multiple variances was used to calculate the prevalence ratio and their respective 95% confidence intervals. RESULTS: The prevalence of anxiety and severe depressive symptoms of 22.74% and 6.71% respectively was found. Depressive symptoms RPa 3.274 (95% CI 1.06 - 10.09), having children RPa 2.61 (95% CI 1.26 - 5.38), and the diagnosis of COVID-19 in the last 12 months RPa 2.20 (95% CI 1.25 - 3.87) were associated with the presence of anxiety in the multiple regression model. CONCLUSIONS: The presence of severe depressive symptoms, having children, the diagnosis of covid-19 in the last 12 months are associated with the diagnosis of anxiety in medical interns at a private university in Lima, 2021.